Screening and molecular identification of lipolytic bacteria from spent bleaching earth - SITI SOLEHA; Endah Retnaningrum (Society for Indonesian Biodiversity, 2020)
Abstract. Soleha S, Retnaningrum E. 2020. Screening and molecular identification of lipolytic bacteria from spent bleaching earth. Biodiversitas 21: 4155-4161. Lipolytic bacteria can produce nanobioremediation materials that encourage researchers to explore the diversity of these bacteria. Lipolytic bacteria were isolated from spent bleaching earth (SBE). Bacteria isolates were screened for their lipolytic index and crude lipase activity. Strain with the highest lipolytic index and crude lipase activity were identified using the 16S rRNA gene as genetic markers. The maximum likelihood method in MEGA6 software has been used to analyze the relationship of the isolate. The results showed that strain SBE01 had the highest lipolytic index and crude lipase activity of 8.8 ± 0.7 mm and 5.7 U/mL, respectively. Based on 16S rRNA gene analysis, the isolate was identified as Moraxella sp. Phylogenetic tree was shown that SBE01 isolate was closely related to Moraxella osloensis. Moraxella sp. has the potential to be used as a bioremediation agent from oil-contaminated environment.